Exploring The Emerging Role Of Data Mining In Retail Forecasting : Need For The Retailers (International Journal of Engineering and Computer Science, 2017)
In the modern age the Retail marketing is growing very fast but as fast as it is growing, Different challenges arise for the retailers. The arrival, growth and spread of Information Technology and related tools have revolutionized the way modern day businesses are being conducted at the global as well as national levels. For the Retailers optimum and precise decisions are important in the given dynamic and competitive business environment. Further, forecasting decisions also assume crucial significance across all areas of business with Retail also not being an exception. Forecasting decisions in context of Retail are associated with their own share of challenges and issues. The present working paper seeks to explore the emerging roles of Data Mining in Retail Forecasting as needed for the retailers for better business idea. This work further explores the possible applications of other related IT technologies and also discusses the related issues and trends, so the retailer need to invest less and may be able to earn more.